2018
DOI: 10.1007/s11423-017-9568-4
|View full text |Cite
|
Sign up to set email alerts
|

Supporting learners’ experiment design

Abstract: Inquiry learning is an educational approach in which learners actively construct knowledge and in which performing investigations and conducting experiments is central. To support learners in designing informative experiments we created a scaffold, the Experiment Design Tool (EDT), that provided learners with a step-by-step structure to select variables and to assign values to these variables, together with offering built-in heuristics for experiment design. To further structure the students' approach, the EDT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 42 publications
2
20
0
3
Order By: Relevance
“…In a recent study, the EDT was compared with two control conditions (that guided learners in the form of more or less specific research questions) in order to study the effect of the EDT on learners' conceptual knowledge gains. Results showed that low prior knowledge learners, that is, learners whose conceptual knowledge about the domain did not exceed 25% of a conceptual knowledge test before working with the learning environment, significantly benefited from the EDT (van Riesen et al, 2018b). The results of that study indicated that guidance should fit with learners' prior knowledge about the domain.…”
Section: The Edtmentioning
confidence: 88%
See 1 more Smart Citation
“…In a recent study, the EDT was compared with two control conditions (that guided learners in the form of more or less specific research questions) in order to study the effect of the EDT on learners' conceptual knowledge gains. Results showed that low prior knowledge learners, that is, learners whose conceptual knowledge about the domain did not exceed 25% of a conceptual knowledge test before working with the learning environment, significantly benefited from the EDT (van Riesen et al, 2018b). The results of that study indicated that guidance should fit with learners' prior knowledge about the domain.…”
Section: The Edtmentioning
confidence: 88%
“…Designing experiments is one of the core activities of inquiry learning, situated in the middle of the inquiry cycle as the linchpin between the more theoretical phases of hypothesis generation and drawing conclusions (Osborne, Collins, Ratcliffe, Millar, & Duschl, 2003;van Riesen, Gijlers, Anjewierden, & de Jong, 2018b). Learners must design experiments by which they can obtain results that are relevant for drawing conclusions regarding their hypothesis or research question.…”
Section: A Core Inquiry Process: Designing Experimentsmentioning
confidence: 99%
“…In the course of developing Go-Lab, a series of experimental studies aiming at the student level have been conducted, mainly to measure the effect of specific versions of apps (see e.g., van Riesen et al 2018 ; Efstathiou et al 2018 ; Kuang et al 2020 ). The results of these studies were used for the (re)design of those Go-Lab apps.…”
Section: Research Questions On the Instructional Design Processmentioning
confidence: 99%
“…Our data set does not allow us to see the reasons behind moving from one version of an ILS to the next and we also cannot see whether teachers tried out versions of ILSs with their students before moving to a new version, as is the primary advice in classical instructional design models (see e.g., Branch 2009). Our clear impression, though, is that teachers often used a rapid prototyping approach that is supported by the facilities that Go-Lab offers, in which intermediate versions of the ILS form a basis for self-reflection or discussions with colleagues in order to take the next step (Tripp and Bichelmeyer 1990). Another reason to create a copy can be that once an ILS has been successfully implemented, teachers may create a new copy and share it, sometimes in an adapted form, with a new group of students, to keep the data from different classes separate.…”
Section: Design Process Characteristicsmentioning
confidence: 99%
“…An example of a more specific scaffold (for an overview, see Zacharia et al, ) is an experiment design tool that breaks down the process of experiment design: selecting variables; categorizing them as independent, dependent, or control; assigning values to them; and deciding on the number of trials. An experiment design tool can even suggest specific experimentation strategies such as vary one variable at the time (van Riesen, Gijlers, Anjewierden, & de Jong, ). Finally, combining direct instruction and inquiry can also be supported by technology.…”
Section: Combining Inquiry With (Technology‐based) Pedagogical Guidancementioning
confidence: 99%